1987
DOI: 10.3133/cir987
|View full text |Cite
|
Sign up to set email alerts
|

The use of surface geophysical techniques to detect fractures in bedrock; an annotated bibliography

Abstract: This annotated bibliography compiles references about the theory and application of surface geophysical techniques to locate fractures or fracture zones within bedrock units. Forty-three publications are referenced, including journal articles, theses, conference proceedings, abstracts, translations, and reports prepared by private contractors and U.S. Government agencies. Thirty-one of the publications are annotated. The remainder are untranslated foreign language articles, which are listed only as bibliograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Resistivity methods have been successfully applied to detect fractures by a number of investigators, including Risk (1975), McDowell (1979), Palacky and others (1981), Soonawalaand Deuce (1981), Taylor (1982), Mallik and others (1983), Leonard-Mayer (1984a, 1984b, Ogden and Eddy (1984), Taylor and Fleming (1988), Lieblich and others (1991, 1992a), andRitziand Andolsek (1992. Most of these investigators applied collinear arrays rotated about a fixed center point to measure directional variations in apparent resistivity that are related to sets of similarly oriented steeply dipping fractures (Lewis and Haeni, 1987).…”
Section: Azimuthal Direct-current Square-array Resistivitymentioning
confidence: 99%
“…Resistivity methods have been successfully applied to detect fractures by a number of investigators, including Risk (1975), McDowell (1979), Palacky and others (1981), Soonawalaand Deuce (1981), Taylor (1982), Mallik and others (1983), Leonard-Mayer (1984a, 1984b, Ogden and Eddy (1984), Taylor and Fleming (1988), Lieblich and others (1991, 1992a), andRitziand Andolsek (1992. Most of these investigators applied collinear arrays rotated about a fixed center point to measure directional variations in apparent resistivity that are related to sets of similarly oriented steeply dipping fractures (Lewis and Haeni, 1987).…”
Section: Azimuthal Direct-current Square-array Resistivitymentioning
confidence: 99%
“…An annotated bibliography of surface-geophysical techniques to detect fractures in bedrock is included in Lewis and Haeni (1987). Conventional techniques for hydrologic applications are discussed by Zohdy and others (1984).…”
Section: Surface Geophysical Surveysmentioning
confidence: 99%
“…Two of the geological contexts in which geophysical methods can play an important role in medium-temperature geothermal systems are: systems related to sedimentary basins (Viseras, 2002) and systems related with fractured crystalline rocks (Lewis and Haeni, 1987). Previous studies (Calcagno et al, 2014;Mahajan et al, 2011;Rao, 1986) showed that different physical properties such as density or acoustic impedance reveal a great contrast between the basement and the sedimentary basin.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in fractured crystalline rocks, different physical properties, e.g. the electrical resistivity, can show a great contrast between the fractured and the fresh crystalline rock (Kirkby et al, 2016;Lewis and Haeni, 1987;Mandal et al, 2019;Thanassoulas and Xanthopoulos, 1991). In this way, geophysical methods allow a preliminary delimitation and characterization of the geothermal reservoir, which is essential for the determination of the system magnitude.…”
Section: Introductionmentioning
confidence: 99%